Water caltrop shell-derived nitrogen-doped porous carbons with high CO2 adsorption capacity. (February 2021) - Zhao, Zhenning; Ma, Changdan; Chen, Fangyuan; Xu, Guozhong; Pang, Ruixue; Qian, Xinyue; Shao, Jiawei; Hu, Xin
Abstract: Adsorption via sorbents is considered an attractive technology that can effectively separate CO2 from flue gas. Optimal adsorption performance can be achieved through the utilization of specific sorbents with superior CO2 adsorption capacity. This work demonstrates the conversion of water caltrop shell into N-doped porous carbons for CO2 capture, which involves a three-step procedure, i.e., carbonization of water caltrop shell, post-nitriding by melamine, and KOH activation. The developed adsorbents possess plentiful porous structures and high nitrogen content, with BET surface area up to 2384 m 2  g −1 and N content of 8.48 wt%, respectively. CO2 adsorption measurements show that the studied sorbents have good CO2 adsorption abilities, as high as 4.22 and 6.06 mmol g −1 at 25 and 0 °C under ambient pressure, respectively. A comprehensive investigation found that CO2 uptake of as-synthesized adsorbents is dictated by the synergistical interplay of N content and narrow microporous volume. Additionally, they exhibit fast CO2 adsorption kinetics, excellent reversibility and stability, good CO2 /N2 selectivity, applicable heat of adsorption and high dynamic CO2 adsorption capacity. This work provides a general method of the preparation of N-doped porous carbonaceous sorbents from waste biomass. The inexpensiveness precursors along with simple preparation procedure highlight the great potential of biomass-based carbons in CO2 capture and many other applications. Graphical abstract: Image 1 Highlights: N-enriched charcoal was obtained by melamine nitriding of carbonized water caltrop shell. Porous carbons with high nitrogen content up to 8.48 wt% were synthesized by KOH activation. Water caltrop shell derived carbon exhibits high CO2 uptake, 6.06 mmol/g at 0 °C and 1 bar. Combined interplay of nitrogen content and narrow microporous volume determines the CO2 uptake.